2020
DOI: 10.1111/nph.16456
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and water potential co‐limit stem cambial activity along a steep elevational gradient

Abstract: Efforts to develop mechanistic tree growth models are hindered by the uncertainty of whether and when tree growth responses to environmental factors are driven by carbon assimilation or by biophysical limitations of wood formation.In this study, we used multiannual weekly wood-formation monitoring of two conifer species (Larix decidua and Picea abies) along a 900 m elevational gradient in the Swiss Alps to assess the biophysical effect of temperature and water potential on wood formation. To this end, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 116 publications
5
66
0
Order By: Relevance
“…However, high temperatures probably act together with low precipitation to cause the observed drought-induced cessation or slowing of wood formation (Cabon et al, 2020; also seen in our soil moisture simulations), similar to Mediterranean systems (Cabon et al, 2018;Lempereur et al, 2017). Another indirect effect of temperature may have been to act on stem water potential via the influence on vapour pressure deficit.…”
Section: Mechanisms and Drivers Involved In Growth Increment Dynamicssupporting
confidence: 66%
See 1 more Smart Citation
“…However, high temperatures probably act together with low precipitation to cause the observed drought-induced cessation or slowing of wood formation (Cabon et al, 2020; also seen in our soil moisture simulations), similar to Mediterranean systems (Cabon et al, 2018;Lempereur et al, 2017). Another indirect effect of temperature may have been to act on stem water potential via the influence on vapour pressure deficit.…”
Section: Mechanisms and Drivers Involved In Growth Increment Dynamicssupporting
confidence: 66%
“…Indeed, it has been suggested that ongoing climate warming in this area (King et al, 2013) has made this and nearby sites less sensitive to direct growth limitations by temperature (Cabon et al, 2020), with maybe the exception of growth onset (Cuny et al, 2019).…”
Section: Mechanisms and Drivers Involved In Growth Increment Dynamicsmentioning
confidence: 99%
“…Our analysis evidenced that LBM defoliation effects were not the same for all xylem functional traits. This indirectly indicates that xylogenesis phases of cambial division, cell enlargement, and cell wall thickening are differently affected not only by temperature and water (Castagneri et al, 2017;Cabon et al, 2020b), but also by carbon availability. Specifically, lumen size was reduced in the first two to three years of outbreak, but to a lesser extent than cell-wall thickness and cell number, confirming our initial hypothesis.…”
Section: Discussion Lbm Outbreak Effects On Cell Anatomical Featuresmentioning
confidence: 99%
“…2020b). Similarly, growth cessation in autumn may involve responses to day length (Baba et al 321 2011), temperature (Begum et al 2016), or even drought (Ziaco et al 2016, Cabon et al 2020b. 322…”
Section: Discussion 251mentioning
confidence: 99%